PENGARUH pH PADA PROSES KOAGULASI DENGAN KOAGULAN ALUMINUM SULFAT DAN FERRI KLORIDA - Wardani, Rachmawati S.; Iswanto, Bambang; Winarni, Winarni (Jurnal Teknologi Lingkungan Universitas Trisakti, 2009)
Influence of pH in the Coagulation Process Using Aluminum Sulphate and Ferric Chloride. Coagulation occurs by interaction of coagulant with the contaminant such as colloidal particles. Coagulation process influences by several factors i.e. pH, dosages, and turbidity. This research studies the influence of pH and dosages in the coagulation and flocculation process using aluminum sulphate (Al2(SO4)3..14,3H2O ) and ferric chloride (FeCl3.6H2O). Artificial suspensions using kaolin represents high turbidity suspension (124 NTU) and medium turbidity suspensions (51 NTU) are prepared in this research. Result suggests pH and dosages has significant impact for aluminum sulphate, whereas ferric chloride provides a wider range of pH than aluminum sulphate.